Differential gene expression profiling of Listeria monocytogenes in Cacciatore and Felino salami to reveal potential stress resistance biomarkers. (April 2015) - Mataragas, M.; Rovetto, F.; Bellio, A.; Alessandria, V.; Rantsiou, K.; Decastelli, L.; Cocolin, L.
Abstract: The current study reports a) the in situ transcriptional profiles of Listeria monocytogenes in response to fermented sausage stress and b) an approach in which in situ RT-qPCR data have been combined with advanced statistical techniques to discover potential stress resistance or cell viability biomarkers. Gene expression profiling of the pathogen has been investigated using RT-qPCR to understand how L. monocytogenes responds to the conditions encountered during the fermentation and ripening of sausages. A cocktail of five L. monocytogenes strains was inoculated into the batter of Cacciatore and Felino sausages. The RT-qPCR data showed that the acidic and osmotic stress-related genes were up-regulated. The transcripts of the lmo0669 gene increased during the fermentation and ripening of Cacciatore, whereas gbuA and lmo1421 were up-regulated during the ripening of Felino and Cacciatore, respectively. sigB expression was induced in both sausages throughout the whole process. Finally, the virulence-related gene prfA was down-regulated during the fermentation of Cacciatore. The multivariate gene expression profiling analysis suggested that sigB and lmo1421 or sigB and gbuA could be used as different types of stress resistance biomarkers to track, for example, stress resistance or cell viability in fermented sausages with short (Cacciatore) or long (Felino) maturation times, respectively. Highlights: A cocktail of Listeria monocytogenes was inoculated into the batter of Italian sausages. The gene expression profiling of the pathogen was investigated using RT-qPCR. RT-qPCR data showed that acid and osmotic stress-related genes were up-regulated. sigB, lmo1421 and gbuA might be used as of stress resistance biomarkers.